The Effect of Environmental Knowledge Level on Environmental Care Attitudes in the GBPLHS Program Elementary School in Padang City - Rachma Deli Fachrin; Skunda Diliarosta; Nurhasan Syah; Nasfryzal Carlo (International Journal of Educational Dynamics, 2022)
This research was conducted to determine the extent to which the level of environmental knowledge influences the attitude of caring for the environment in the GBPLHS program in Padang City. The research method uses simple regression analysis with SPSS 21. Based on the results of the analysis it can be concluded that there is a positive and significant influence between knowledge of environmental care attitudes in the GBPLHS program in Padang City. The more knowledge increases, the higher the attitude of caring for the environment in students of elementary school 02 Terandam and elementary school 03 Pertiwi.